The range of activities undertaken by minders for the sake of elderly persons - Kachaniuk, Hanna; Wilusz, Agnieszka; Wysokiński, Mariusz; Fidecki, Wiesław; Walas, Lilla (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. Every human being, throughout their life, is both a provider and a recipient of care. A character of care depends on the period of life one goes through and their health state. The range of undertaken activities may refer to strengthening the health state, preventing diseases and injuries, administering treatment, nursing and rehabilitation. Aim. Specifying the range of activities undertaken by minders in order to help elderly persons. Material and methods. The research involved using the diagnostic poll method. A questionnaire form drafted by the authors was used to solve research problems posed in this paper. Statistic analysis was administered by means of a non-parameter test c2 and Pearson’s linear correlation coefficient. Conclusions and results. The majority of those undergoing research, i.e. 78.8% were non-professional minders who were only generally prepared for administering care. It is necessary to carry out educational actions preparing minders for administering care at home. These include teaching nursing techniques and providing necessary information about health and threats to it, as well as about ways to nurse the ill. Elderly persons most often required help with respect to nursing and household maintenance duties. A significant correlation of a = 0.01 was found between the appraisal of the state of health and the appraisal of life made by elderly persons’ minders.